Quality of life is related to fecal calprotectin concentrations in colonic Crohn disease and ulcerative colitis, but not in ileal Crohn disease - Gauss, Annika; Geiß, Thomas; Hinz, Ulf; Schäfert, Rainer; Zwickel, Philipp; Zawierucha, Anna; Stremmel, Wolfgang; Klute, Lukas (Medicine, 2016)
To formulate therapy goals, we aimed to define the relationship between fecal calprotectin and health-related quality of life in inflammatory bowel diseases (IBDs). This retrospective single-center cross-sectional study included ambulatory IBD patients who had completed standardized questionnaires comprising items of health-related quality of life (Short Inflammatory Bowel Disease Questionnaire) and clinical disease activity scores, and who had provided stool samples for calprotectin determination within 30 days of questionnaire completion. Correlation analyses were performed between the indicated parameters. Post hoc analysis was conducted, taking into account only data from patients with fecal calprotectin concentrations measured within 3 days of questionnaire completion. One hundred ninety-seven patients with Crohn disease and 111 patients with ulcerative colitis were enrolled in the study. Lower fecal calprotectin concentrations were associated with better health-related quality of life. The correlations were weak, but stronger if only fecal calprotectin concentrations measured within 3 days of questionnaire completion were included (results for 3 days; Crohn disease: n = 86, rS = −0.419, P < 0.001; ulcerative colitis: n = 43, rS = −0.432, P = 0.004). In Crohn disease, a significant correlation between fecal calprotectin concentration and health-related quality of life was found in patients with colonic involvement (n = 59, rS = −0.470, P < 0.001), but not in patients with purely ileal disease (n = 27, rS = −0.268, P = 0.18). Correlations between fecal calprotectin concentrations and clinical disease activity were also only weak to moderate. Owing to its moderate correlation with fecal calprotectin concentrations in IBD patients with colonic involvement, health-related quality of life should be used in combination with other markers for IBD management. This is even more important in isolated ileal Crohn disease, where no significant correlation between fecal calprotectin concentration and health-related quality of life was found. Especially for use in research studies, care should be taken to keep the time between clinical evaluation of IBD patients and the determination of fecal calprotectin concentrations as short as possible.